Can Fusobacterium utilize nucleomodulins in the pathophysiology of CRC? - Anand, Swadha; Korgaonkar, Sania; Bose, Chandrani (Frontiers in Cellular and Infection Microbiology, 2025)
Fusobacterium nucleatum (Fn) has been appositely termed as “oncobacterium” owing to its high abundance in colorectal tumor tissues throughout the course of tumorigenesis. However, beyond FadA and Fap2, there is a limited understanding of its virulence factors and mode of pathogenesis. Latest studies indicate an association of host genetic and epigenetic modifications with the degree of Fn colonization in tumor tissues. These changes are implicated in rendering the microenvironment more conducive for progression to later stages of tumorigenesis. Recent reports suggest the involvement of strains belonging to Clade C2 within Fn subspecies animalis (Fna C2) in colorectal cancer (CRC) that might have the ability to influence host homeostasis. In this study, we focus on the identification of candidate “nucleomodulins (NMs)”, which are nucleus-targeting effector proteins in Fna using various in silico sequence, structural and molecular dynamics simulation analyses. The results suggest the presence of a set of NMs in Fna, possessing a classical nuclear localization signal (cNLS), which can potentially bind to importin. This catalog of candidate NMs would help in designing experiments toward exploring their potential role in modulating host gene expression and epigenetics by entering the nucleus.